Implementation of a Five-Pillar Diabetes Education Video to Promote Physical Activity among Patients with Type 2 Diabetes Mellitus - Ardin S Hentu; Armawati Abidin; Muh Risal (Fakultas Kedokteran, Universitas Papua, 2026)
Diabetes mellitus is a metabolic disease that progresses gradually and may occur without distinctive symptoms. This study aimed to implement a Five-Pillar Diabetes Education Video to promote physical activity among patients with type 2 diabetes mellitus. The study involved 70 participants, consisting of 35 participants in the intervention group and 35 in the control group. The intervention group received the Five-Pillar Diabetes Education Video accompanied by monitoring twice a week, whereas the control group received the video at the beginning of the intervention and a booklet without home monitoring. The Evidence-Based Nursing Practice process supporting the intervention involved searching for randomized controlled trial articles through PubMed, ProQuest, and Google Scholar using the keyword “Education Video in Diabetic Patients.” A total of 126 relevant articles were identified and screened. Physical activity adherence was assessed before and after the intervention. The mean score in the intervention group increased from 4.86 before the intervention to 6.69 after the intervention, while the control group increased from 6.49 to 6.60. The independent-samples t-test showed significant differences between groups before (p < 0.001) and after the intervention (p = 0.001). These findings indicate an association between implementation of the Five-Pillar Diabetes Education Video and increased physical activity adherence.